1993
DOI: 10.1002/jpln.19931560212
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term nitrogen balance for pearl millet (Pennisetum glaucum L.) in an acid sandy soil of Niger

Abstract: On acid sandy soils of Niger (West Africa) fertilizer N recovery by pearl millet (Pennisetum glaucum L.) is often more than 100 per cent in years with normal or above average rainfall. Biological nitrogen fixation (BNF) by N2‐fixing bacteria may contribute to the N supply in pearl millet cropping systems. For a long‐term field experiment comprising treatments with and without mineral fertilizer (F) and with and without crop residue application (CR) a N balance sheet was calculated over a period of six years (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…shown previously by Hafner et al (1993b). The data Compared with 500 kg CR ha Ϫ1 , the application of 2000 also show the cumulative effects of CR application with kg CR ha Ϫ1 for 2 yr resulted in increases in pH, available time (Fig.…”
Section: Mulching Effects In the Sahelian Zonesupporting
confidence: 66%
See 3 more Smart Citations
“…shown previously by Hafner et al (1993b). The data Compared with 500 kg CR ha Ϫ1 , the application of 2000 also show the cumulative effects of CR application with kg CR ha Ϫ1 for 2 yr resulted in increases in pH, available time (Fig.…”
Section: Mulching Effects In the Sahelian Zonesupporting
confidence: 66%
“…This is supported by Wendt et al (1993), who found that minor changes in availability in the topsoil through increases in root length density as reported by Hafner et al (1993b).…”
Section: Sitesupporting
confidence: 61%
See 2 more Smart Citations
“…Much greater than the issue of soil acidity in terms of pH is the effect of soil acidification on the soil resource itself, particularly the reduction in soil cation exchange capacity (Barak et al, 1998). The addition of small amounts of crop residues in combination with inorganic fertilizers can counteract soil acidification (de Ridder and van Keulen, 1990) and increase soil cation exchange capacity (Bationo et al, 1995; de Ridder and Van Keulen, 1990), populations of N‐fixing bacteria, and root length and density, leading to an increase in total P uptake by the crop (Hafner et al, 1993a, 1993b). The partial rather than total removal of crop residues from fields is vital for these benefits to be realized.…”
Section: Nutrient Cycling In Mixed Farming Systemsmentioning
confidence: 99%